Acorn Oil: Chemistry and Functionality - Mehdi Taib; Lahboub Bouyazza; Badiaa Lyoussi (Journal of Food Quality)
Acorn oil has been receiving increasing attention due to its nutritional potentials. However, its application as a novel food ingredient has not yet been fully explored. This paper summarizes chemical composition, extraction methods, potential health benefits, and current applications of acorn oil, with the aim of providing suggestions for its exploitation. Acorn oil is an excellent source of essential fatty acids (oleic, linoleic, α-linolenic, and palmitic acids). Acorns are a rich source of tocopherols, with γ-tocopherol being the most abundant. It also contains various bioactive compounds such as polyphenols and sterols (mainly β-sitosterol). Diets enriched with acorn oil can be beneficial in preventing cardiovascular disease (CVD), cancer, and type 2 diabetes as well as offer antioxidant activity. Further studies should focus on producing better quality acorn oil such as the application of more innovative and optimized techniques that can increase its health benefits and hence utilization.